Compliance of Pharmacy Service Standards at The Phcussia of Banjarmasin City - Nufus, Hayatun; Aryzki, Saftia; Malahayati, Siti; Kurniawati, Darini (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Pharmaceutical work carried out in the acquisition, production, distribution and maintenance of drugs must be carried out by health workers who have the appropriate knowledge and authority for that. Based on the description above, researchers are very interested in knowing whether or not there is a conformity of pharmaceutical service activities in all Banjarmasin city health centers based on Permenkes RI No. 26 of 2020 related to Pharmaceutical Service Standards. The purpose of this study was to determine the suitability of Pharmaceutical Services at public health center in Banjarmasin City against Permenkes No. 26 of 2020 concerning Pharmaceutical Service Standards at public health center. The research design method used is observation, namely making direct observations accompanied to obtain information on the Management of Pharmaceutical Supplies and Consumable Medical Materials, as well as Clinical Pharmacy Services. There are 26 health centers in Banjarmasin City. All health centers have met the suitability of pharmaceutical preparation management and Medical Consumables (BMHP) in accordance with the Minister of Health Regulation No. 26 of 2020. However, 10 public health center in Banjarmasin City have not met the requirements of clinical pharmacy services, such as Counseling, Monitoring Drug Side Effects, Monitoring Drug Therapy, and Evaluating Drug Use. This is influenced by limited human resources at these health centers. 26 health centers in Banjarmasin City are appropriate in managing pharmaceutical preparations and Consumable Medical Materials (BMHP) and 16 health centers are appropriate in implementing clinical pharmacy services.